The Effect of the Lumbar Pedicle and Pediculo-Corporal Junction Histology on the Pedicle Screw Insertion Technique: pediculocorporal junction - Yilmaz, Murat; Alkis, Beyza; Yucesoy, Kemal (Open Access Macedonian Journal of Medical Sciences, 2020)
Background: Posterior lumbar pedicle screw instrumentation has gained a wide acceptance in the treatment of the various spinal lesions requiring fusion. Inserting screws into the pedicles take a great deal of skill, as the dense bony parts are not large, and a mistake could push a bone fragment into the spinal nerves, causing pain, loss of mobility and other damage. Aim: To investigate the histological and gross-anatomical properties of the pediculocorporal junction, which can have important clinical implications on the insertion technique of the pedicle screws. Study Design: This study was approved by the University Clinical Center Review Board. Human cadaveric lumbar spinal segments which were fixed with formaldehyde were used in the study. Methods: Twenty pedicles from 10 lumbar spinal segments (L3-L5) were prepared for histological and gross-anatomical investigation. Thin slice cuts were taken from the specimens and examined histologically and macroscopically. Results: There were not any differences in the histological characteristics of the pedicles and the pediculo-corporal junction. Thin compact osseous formation or web like connective tissue formation was not identifiable in the pediculo-corporal junction. Conclusion: All kind of pedicle screws can be attempted to be inserted just after preparation of the insertion point with an awl or just decortication of the entrance point with a rongeur. This can also reduce the pilot hole preparation technique related complications like perforation of the pedicle walls.